A review of “music and movement” therapies for children with autism: embodied interventions for multisystem development - Bhat, Anjana N.; Srinivasan, Sudha (Frontiers in Integrative Neuroscience, 2013)
The rising incidence of Autism Spectrum Disorders (ASDs) has led to a surge in the number of children needing autism interventions. This paper is a call to clinicians to diversify autism interventions and to promote the use of embodied music-based approaches to facilitate multisystem development. Approximately 12% of all autism interventions and 45% of all alternative treatment strategies in schools involve music-based activities. Evidence suggests that musical training significantly impacts various forms of development including communication, social-emotional, motor, and behavioral development, in children with ASDs, typically developing individuals, and children with other neurological disabilities such as dyslexia and intellectual disabilities. In this review, we first highlight mechanisms and evidence for how music and movement interventions can enhance communication, social-emotional, behavioral, and motor skills in individuals with autism. We will support our claims by reviewing results from brain imaging studies in children with autism that provide neuroanatomical evidence for the effects of music therapies in autism. We will also discuss the critical elements and the different types of music therapy approaches commonly used in pediatric neurological populations including autism. We provide strong arguments for the use of music and movement interventions as a multisystem treatment tool for children with ASDs. Finally, we also make recommendations for assessment and treatment of children with ASDs, and provide directions for future research.